Optimasi Sumberdaya Air dengan Program Linear (Linear Programming) di DAS Cicatih, Kabupaten Sukabumi, Jawa Barat - Roh Santoso Budi Waspodo; Siti Komariah; Vita Ayu Kusuma Dewi (PERTETA, 2019)
The used of water in Indonesia for various using disposed exceed water supply. One of the efforts to optimize limited water resources is optimimation watershed management with linear programming. Identification of surface water potential in Cicatih watershed, especially in sub-watershed of upper Cicatih, Cibojong river, estimate using GR4J model. This research using discharge data from PLTA Ubrug. Springwater identified based on data from DISTAMBEN. The observation discharge average in Cibojong river was 246 l/s/day and based on GR4J model was 2752 l/s/day. Avaiable discharge was 56241 l/s/day. Grow of the population estimated by exponent method, industry and irrigation area with regression linear. Software Lingo 8.0 was used to help optimize of wáter resources in Cicatih watershed. Based on the result, in 2025, 12 industries and 15784 ha area get the wáter allocation from surface water. About 1083817 people and 75402 ha area get from springwáter. The cost to access surface wáter is higher than in other sectors. It causes the industry to gets an allocation from surface wáter.